Epilepsy-related functional brain network alterations are already present at an early age in the GAERS rat model of genetic absence epilepsy - Wachsmuth, Lydia; Hebbelmann, Leo; Prade, Jutta; Kohnert, Laura C.; Lambers, Henriette; Lüttjohann, Annika; Budde, Thomas; Hess, Andreas; Faber, Cornelius (Frontiers in Neurology, 2024)
Genetic Absence Epilepsy Rats from Strasbourg (GAERS) represent a model of genetic generalized epilepsy. The present longitudinal rs-fMRI study in GAERS and age-matched non-epileptic controls (NEC) aimed to characterize the epileptic brain network using two functional measures, resting statefunctional magnetic resonance imaging (rs)-fMRI) and manganese-enhanced MRI (MEMRI) combined with morphometry, and to investigate the potential progression of brain network changesalterations, following long-term seizure activity.Repeated rs-fMRI measurements at 9.4 T between 3 and 8 months of age were combined with MEMRI at the final time point of the study. We used graph theory analysis to infer community structure and global and local network parameters from rs-fMRI data and compared them to brain region-wise manganese accumulation patterns and deformation-based morphometry (DBM).Functional connectivity (FC) was generally higher in GAERS when compared to NEC. Global network parameters and community structure were similar in NEC and GAERS, suggesting efficiently functioning networks in both strains. No progressive FC changes were observed in epileptic animals. Network-based statistics (NBS) revealed stronger FC within the cortical community, including regions of association and sensorimotor cortex, and with basal ganglia and limbic regions in GAERS, irrespective of age. Higher manganese accumulation in GAERS than in NEC was observed in the brains of at 8 -months -of ageold GAERS than in NEC, consistent with higher overall rs-FC, particularly in sensorimotor cortex and association cortex regions. Functional measures showed less similarity in subcortical regions. Whole brain volumes of 8-months-old GAERS were higher when compared to age-matched NEC, and deformation-basedDBM analysis revealed increased volumes of several association and sensorimotor cortex regions and of the thalamus.Rs-fMRI, MEMRI and volumetric data collectively suggest the significance of cortical networks in GAERS, which correlates with an increased fronto-central connectivity in childhood absence epilepsy (CAE). Our findings also verify involvement of basal ganglia and limbic regions. Epilepsy-related network alterations are already present in juvenile animals. Consequently, this early precondition seems to play a greater role in dynamic brain function than persistent damage caused by chronic absence seizures.